Developing a collaborative knowledge sharing framework to promote english learning retention - Saeheaw T. (2014)
To continue development as a leading Southeast Asian economy, and meet the needs of a knowledge-based society, Thailand must improve English language proficiency. This paper presents an innovative knowledge sharing framework targeting software engineering students' written English skill, by integrating four learning theories; constructionism, cognitive learning, cone of experience and the learning pyramid. Together, these theories promote 'learning by doing' as the most effective way to improve students' English. Results show statistically significant improvements in students' English and suggest the new framework can change the dominant memorisation and recall methods in Thai education to reach higher levels of learning. Copyright © 2013 Inderscience Enterprises Ltd.